Correlation between Degenerative Changes and Osteoporosis in Lumbar Spine of Elderly Women in Dhaka city, Bangladesh (City Dental College Journal, 2018)
Aims: Degenerative joint diseases and decreased bone mass i.e.  osteoporosis are two common age related skeletal disorders  responsible for pain and disability. Bangladesh has a high incidence  of osteoporosis and the incidence particularly in women, occurs  among a relatively younger age group than in the developed world.  However little is known about the correlation between degenerative  changes and osteoporosis in lumbar spine of elderly women. The  purpose of this study was to clarify this relationship in elderly women  of Dhaka, Bangladesh.  Methods: A cross-sectional study was conducted at the department  of radiology and imaging of Bangladesh institute of research and  rehabilitation in diabetes, endocrine and metabolic disorders  (BIRDEM), Dhaka during the period of 1st January, 2009 to 31st  December, 2010. DEXA scan of spine and BMD measurement were  done at a renowned private hospital of Dhaka. Total 63 elderly female  aged between 50-75 years were randomly selected for this study.  Results: An inverse relationship between osteoporosis and  spondylosis in postmenopausal women as evaluated by bone  mineral density and semiquantitative scoring of spinal degeneration  was observed. A significant negative correlation (r=-0.53:p